Work-Related Factors, Exercise Habits, and Individual Characteristics on Musculoskeletal Disorders among Indonesian Young Dentists - Arti, Dwi Windu Kinanti; Prachaiboon, Tiwakron; Aprillia, Zita; Prasetio, Diki Bima (Jurnal Kesehatan Masyarakat, 2025)
MSDs disorders among dentists are one of the most common complaints. This study aims to explore risk factors that can increase the incidence of MSDs among young dentists. Methods: This study used a cross-sectional design with a population of 162 who will be used as the entire sample. The questionnaire instrument contains questions about gender, age, weight, height, smoking habits, how long to sleep in a day, exercise habits, length of work and length of service. There is also a standard questionnaire , namely the Nordic Body Map to evaluate musculoskeletal disorders in individuals. Data analysis used the chi-square test and multiple logistic regression test. Results: The highest MSDs were reported to occur in the upper back (69.8 % ) followed by the lower back (67.3%) and neck (63.6%) while the lowest prevalence was reported in the ankle (8.6%). Gender, length of service, length of service and exercise habits are associated with the occurrence of MSDs. Conclusion: The prevalence of MSDs among young dentists is still high. Length of service is the most influential risk factor.